JOB PERFORMANCE OF ADMINISTRATIVE EMPLOYEE IN SURABAYA: THE ROLE OF WORK ENVIRONMENT AND CAREER DEVELOPMENT - Singkali, Enrico Kevin; Wulani, Fenika; Nagel, P. Julius F. (Research In Management and Accounting (RIMA), 2023)
This research aims to identify the impact of work environment and career development on job performance. Data was collected by distributing questionnaires to administrative employees in Surabaya. The data collected and can be used in hypothesis testing are 101 respondent data. Hypothesis testing was carried out using multiple linear regression in the SPSS 23.0 program. The findings of this study support the research hypothesis, namely that work environment and career development significantly have a positive effect on job performance of administrative employees in Surabaya